1986
DOI: 10.1111/j.1365-2621.1986.tb10844.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Temperature Dependence of Flow Behavior of Xanthan Gum Dispersions

Abstract: Apparent viscosities of xanthan gum dispersions over shear rates of 0.5-3000~s' were studied at concentrations of 0.05-I .OO% (w/w) and temperatures of 5-45"C. All dispersions were shear rate thinning nonNewtonian fluids described accurately by the power-law model. The logarithm of viscosity varied with the logarithm of concentration and the reciprocal of absolute temperature. A combined model was derived to describe the variation of viscosity with shear rate, concentration and temperature for aqueous dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 10 publications
(16 reference statements)
7
47
0
3
Order By: Relevance
“…Segundo Speers [30] , a magnitude de n e a dependência dos valores com a concentração em solução aquosa são dependentes do tamanho das moléculas.…”
Section: Resultado E Discussãounclassified
“…Segundo Speers [30] , a magnitude de n e a dependência dos valores com a concentração em solução aquosa são dependentes do tamanho das moléculas.…”
Section: Resultado E Discussãounclassified
“…(2), then it may also be possible to organize the rate constant and the equilibrium gel strength with respect to temperature using an Arrheniustype relationship. Models of this type have been used in this laboratory to predict the change in viscosity of some drilling fluid constituents such as xanthan gum [6]. The Arrhenius equation can be expressed as:…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…According to Cepeda and Villaran [22], temperature influence on viscosity has been found to be related to soluble solids content, and experimental data for fixed concentrations can be related to the temperature using the Arrhenius-Guzman equation. Many researchers reported that flow behavior index (n) of juices varies only slightly with temperature and moisture content and used a combined model (Equation (1)) to describe their effect on flow consistency index (K) values [20,23,24]:…”
Section: Introductionmentioning
confidence: 99%